Data from: Repeat disturbances have cumulative impacts on stream communities - Haghkerdar, Jessica M.; McLachlan, Jack R.; Ireland, Alexis; Greig, Hamish S. (Dryad, 2019)
(1) Climate change has altered disturbance regimes in many ecosystems, and
predictions show that these trends are likely to continue. The frequency
of disturbance events plays a particularly important role in communities
by selecting for disturbance-tolerant taxa. (2) However, ecologists have
yet to disentangle the influence of disturbance frequency per se and time
since last disturbance, because more frequently disturbed systems have
also usually been disturbed more recently. Our understanding of the
effects of repeated disturbances is therefore confounded by differences in
successional processes. (3) We used in-situ stream mesocosms to isolate
and examine the effect of disturbance frequency on community composition.
We applied substrate moving disturbances at five frequencies, with the
last disturbance occurring on the same day across all treatments.
Communities were then sampled after a recovery period of 9 days. (4)
Macroinvertebrate community composition reflected the gradient of
disturbance frequency driven by differential vulnerability of taxa to
disturbance. Diversity metrics, including family-level richness,
decreased, reflecting a likely loss of functional diversity with
increasing disturbance frequency. In contrast, overall abundance was
unaffected by disturbance frequency as rapid recovery of the dominant
taxon compensated for strong negative responses of disturbance-vulnerable
taxa. (5) We show that cumulative effects of repeated disturbances—not
just the time communities have had to recover before sampling—alter
communities, especially by disproportionately affecting rare taxa. Thus,
the timing of past disturbances can have knock-on effects that determine
how a system will respond to further change.
haghkerdar-comm-matrix_EandE2019Family-level community data from
macroinvertebrate samples collected from stream mesocosms following
various disturbance frequencies. "block" refers to three
longitudinal blocks along the course of the stream reach studied;
"channel" is an individual stream mesocosm; “disturbances” are
the cumulative number of disturbances experienced prior to sampling,
7-Sep-2014. Note that the column titled “Zygoptera” refers to F:
Calopterygidae only.Chironomid and FPOM data, both sampling datesNumber of
chironomid larvae and amount of fine particulate organic matter collected
at two field sampling dates. "block" refers to three
longitudinal blocks along the course of the stream reach studied;
"channel" is an individual stream mesocosm; “disturbances” are
the cumulative number of disturbances experienced by sampling;
"dateID" 1= 29-Aug-2014, 2= 7-Sep-2014 (note that number of
disturbances varies between dates as described in manuscript).
Chironomidae = chironomid abundance; FPOMg = ash-free dry mass of fine
particulate organic matter.haghkerdar-chiron-FPOM-EandE2019.csv
Keywords: macroinvertebrate